Pengaruh Kualitas Sustainability Report dan Board Gender Diversity terhadap Kualitas Laba: Studi Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia pada Tahun 2018-2021 - Arifah Wulandari Marta; Salama Taqwa (Universitas Negeri Padang, 2024)
This research aims to examine the influence of the quality of the Sustainability Report and Board Gender Diversity on earnings quality. The population used in this research is all companies listed on the Indonesia Stock Exchange in the 2018-2021 period. The sampling technique was carried out using a purposive sampling technique, there were 58 companies sampled with observations for 4 years (2018-2021). Profit quality with the Quality Sustainability Report is measured by a disclosure index based on the GRI Standard with a Triple Bottom Line approach (economic, environmental and social). The research results show that in the 2018-2021 observations, the quality of the Sustainability Report had a positive effect on earnings quality and Board Gender Diversity had a negative effect on earnings quality. Future research, focusing on one industrial sector, adding other independent variables and adding a longer time span to the research will provide better results.